The state-of-the-art technologies for medical dental practice - Sańpruch, Łukasz; Wiench, Rafał; Marków, Magdalena; Urbaniak, Monika; Misiołek, Maciej (Journal of Stomatology, 2017)
Roentgen-diagnostics holds one of the major positions in dental diagnostic procedures. Recent years have seen booming development of such techniques, basically due to improving computer software. This has been true for both, digital radiography and some novel solutions. Cone tomography, or the volume one, both refer to the same diagnostic technique. Commonly used in Poland has been the notion of “volume tomography” after the original English name of Digital Volume Tomography (DVT), although it seems more accurate to use the name of “cone tomography referring to Cone Beam Computed Tomography (CBCT) . Used for X-ray visualisation of hard tissues in the craniofacial area, it denotes procedures applying a specific unit – volume CT scanner – or 3D pantomography.